2016
DOI: 10.1075/sibil.51.10fue
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of grammatical gender in L1 bilingual Spanish

Abstract: We analyze the emergence of grammatical gender in the spontaneous longitudinal Spanish production of a set of Spanish/English bilingual twins from the FerFuLice corpus (Fernández Fuertes & Liceras 2009). We take as a point of departure theoretical accounts on gender assignment and gender concord and previous empirical work on the acquisition of gender by monolinguals and bilinguals. Our study deals with how gender incorporates in the case of L1 Spanish bilinguals; how concord within the determiner phrase (DP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This range allowed for a subdivision of the bilingual group into three cohorts of interest: simultaneous bilinguals (AOB 0–3 years; n = 21), early sequential child bilinguals (AOB 4–6 years; n = 37), and late sequential child bilinguals (AOB 7–10 years; n = 17). AOBs of 4 and 7 years were chosen as cutoffs based on neuroimaging evidence that has suggested that sensitive periods occur around these ages (for review, see Meisel, 2009) but also based on developmental data given that the acquisition of grammatical gender in Spanish is believed to be completed prior to age 4 years (Fernández Fuertes et al., 2016; Montrul, 2004). Appendix S2 in the online Supporting Information provides additional information about the AOB subgroups and about participants removed from the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This range allowed for a subdivision of the bilingual group into three cohorts of interest: simultaneous bilinguals (AOB 0–3 years; n = 21), early sequential child bilinguals (AOB 4–6 years; n = 37), and late sequential child bilinguals (AOB 7–10 years; n = 17). AOBs of 4 and 7 years were chosen as cutoffs based on neuroimaging evidence that has suggested that sensitive periods occur around these ages (for review, see Meisel, 2009) but also based on developmental data given that the acquisition of grammatical gender in Spanish is believed to be completed prior to age 4 years (Fernández Fuertes et al., 2016; Montrul, 2004). Appendix S2 in the online Supporting Information provides additional information about the AOB subgroups and about participants removed from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to its binary gender system and highly reliable pattern of cues to gender values, gender agreement is an early-acquired property in Spanish. Spanish-speaking children raised monolingually acquire gender agreement by age 3 years (for reviews, see Fernández Fuertes, Álvarez de la Fuente, & Mujcinovic, 2016;Montrul, 2004), as do bilingually raised children learning Spanish as one of two L1s as simultaneous bilinguals (Fernández Fuertes et al, 2016). In contrast, heritage Spanish speakers evince difficulties with gender agreement that persist beyond early childhood (for review, see Montrul, 2004Montrul, , 2008Montrul, , 2016.…”
Section: Grammatical Gender In Spanish and Its Acquisitionmentioning
confidence: 99%
“…There is some evidence that, like monolingual children, bilingual children acquiring Spanish in a context where Spanish is the dominant language acquire determiner–noun and noun–adjective gender agreement by age three. Fernández Fuertes et al (2016) investigated the development of grammatical gender in a corpus of conversations with bilingual twins in Spain who were recorded between ages 1;01 to 5;09. Overall, the twins produced 84% target-like gender agreement with determiners and adjectives.…”
Section: Child Heritage Speakers’ Acquisition Of Spanish Gender Agreementioning
confidence: 99%